ANALISIS KOMPARASI RASIO KEUANGAN SEBELUM DAN SELAMA PANDEMI COVID-19 PADA BPR DI PROVINSI BALI - Ni Luh Gede Rahma Dewi (Hita Akuntansi dan Keuangan, 2022)
The Covid-19 pandemic has had a significant impact on the economy, especially in the banking sector. The economic downturn caused the banking performance to decline. Performance is shown in various financial ratios. This research aims to find out whether there are differences between the ratios of CAR, NPL, BOPO, LDR and ROA at BPRs in Bali Province before and during the Covid-19 pandemic. The population in this study is BPR in Bali which reaches 133 BPR. The sample method used purposive sampling which was analyzed by paired sample t-test. The results of the study illustrate that there is no difference in the values of CAR, BOPO, and ROA of BPRs in Bali before and before the Covid-19 pandemic. There are differences in the NPL and LDR values of BPRs in Bali before and before the Covid-19 pandemic.